Needs Analysis: Development of Web-Based Learning Media on Chemical Bond Concepts - Nurhafidhah Nurhafidhah; Hasby Hasby; Muhammad Nazar; Sirry Alvina (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
The study aims to explain the need for developing web-based learning media on chemical bonding concepts. This research is descriptive research with a survey method. The sample of this research is the teacher of chemistry subject who teaches chemical bonding concepts at Senior High School in Langsa city. Data collection techniques using questionnaires, interviews, and documentation. The data collected is data on needs on aspects of teacher readiness, student needs, and support. Data analysis uses descriptive qualitative and quantitative descriptive analysis techniques. The results showed that teachers of chemistry subjects at Senior High School in Langsa City had the readiness to use web-based learning media that would be developed. Based on the teacher's response, the development of web-based learning media on chemical bonding material is strongly needed by teachers and students. The support of facilities and human resources at Senior High School in Langsa City on web-based learning media apply is adequate. These results concluded that the development of web-based learning media on chemical bonding material is strongly needed in chemistry lessons at senior high school in Langsa city.